UTILIZING SCIENTIFIC APPROACH TO IMPROVE STUDENTS' SCIENCE PROCESS SKILLS - Yani Yani (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
This research was motivated by the learning process which was still teacher-centered, in which the teacher's role was more dominant in providing materials and sometimes presenting demonstrations. As a result, the student activities were not facilitated so that their science process skills were less honed. This study aimed to improve students' science process skills through scientific approach. This research is a classroom action research conducted on students at SDN 019 Sungai Raya grade 1 totaling 25 students. The instruments used in this research were the observation sheet and the science process skills test. The results showed that the students’ science process skills in Cycle I had an average percentage of 72.8% with high category and it increased in Cycle II to 83.6% with very high category. Based on the research results, it could be concluded that cientific approach improved the science process skills of the 4th grade students at SDN 019 Sungai Raya.